Sp1 and Egr1 Regulate Transcription of the Dmrt1 Gene in Sertoli Cells - Lei, Ning (2002)
Dmrt1 is a recently described gene that is specifically expressed in the gonads and is required for postnatal testis differentiation. Here, we describe the transcriptional mechanisms regulating the Dmrt1 proximal promoter in testicular Sertoli cells. A genomic clone containing exon 1 of the rat Dmrt1 gene and more than 9 kilobases of 5′ flanking sequence was isolated and characterized. Several prominent transcriptional start sites were identified, with the major site located 102 bases from the translational start. The Dmrt1 5′ flanking region from −5000 to + 74 was transcriptionally active in primary Sertoli cells, and deletion analysis of this fragment identified 2 major regions needed for full Dmrt1 promoter function. These regions were located between −3200 and −2000 base pairs (bp) and downstream of −150 bp relative to the major transcriptional start site. DNase I footprint analysis of the region downstream of −150 bp revealed 3 regions that are bound by proteins from Sertoli cell nuclear extracts. Site-directed mutagenesis of these regions identified 2 elements that activate the Dmrt1 promoter and 2 that repress it. The positive elements bind the transcription factors Sp1, Sp3, and Egr1, suggesting that these transcription factors play a critical role in Dmrt1 regulation in the testis.